2020
DOI: 10.4236/ojf.2020.104024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Contribution of Trees Outside Forests for Income of Rural Livelihoods of Terai Region of Nepal

Abstract: Trees Outside Forests (TOF) is a reliable source of income for farmers in rural area but study regarding this has not been explored in depth yet. Therefore, this study was objectively conducted to assess the contribution of income from TOF products in annual income of rural household. Dhangadimai Municipality of Siraha district, Nepal was selected as study site. Altogether, 300 household surveys and 20 Focus Group Discussions (FGD) were conducted to find the income sources and their contribution including TOF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Similar results are found in India (FSI, 2011;Ghosh & Sinha, 2018) as well as in Kerala, India (Krishnankutty et al, 2008). But Yadav et al (2020) reported higher percentage of timber production (25.17%) from TOF in Dhangadhi Municipality, Siraha district, Nepal which is due to more distribution of planted tree species with wider DBH there.…”
Section: Market Value Of Merchantable Woodsupporting
confidence: 78%
“…Similar results are found in India (FSI, 2011;Ghosh & Sinha, 2018) as well as in Kerala, India (Krishnankutty et al, 2008). But Yadav et al (2020) reported higher percentage of timber production (25.17%) from TOF in Dhangadhi Municipality, Siraha district, Nepal which is due to more distribution of planted tree species with wider DBH there.…”
Section: Market Value Of Merchantable Woodsupporting
confidence: 78%
“…In this context, TOFs play a vital role in providing essential sources of timber, fuel, food, and income [ 83 ]. In addition, TOFs can play a crucial role as forest substitutes, providing rural communities with access to essential livelihood products such as fuelwood, fodder, and timber [ 84 , 85 ]. Harnessing this opportunity not only provides economic support to local communities, reducing their dependence on external purchasing power, but also promotes job creation and strengthens the resilience of these populations [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TOFs can play a crucial role as forest substitutes, providing rural communities with access to essential livelihood products such as fuelwood, fodder, and timber [ 84 , 85 ]. Harnessing this opportunity not only provides economic support to local communities, reducing their dependence on external purchasing power, but also promotes job creation and strengthens the resilience of these populations [ 85 , 86 ]. On the other hand, TOFs offer numerous opportunities focused on climate change mitigation due to the ecosystem services they provide, such as carbon storage [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown higher tree carbon storage in a pine-dominated forest than in a mixed forest of a mid-hill city area (Aryal et al, 2013). Furthermore, different researchers have carried out similar studies on the carbon stock of trees outside the forest showing their importance (Yadav et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 92%